Impact of nitrogen supply on growth, steviol glycosides and photosynthesis in Stevia rebaudiana Bertoni. (2nd September 2016) - Tavarini, S.; Pagano, I.; Guidi, L.; Angelini, L. G.
Abstract : This work investigated the agronomic, physiological and biochemical response of Stevia rebaudiana Bertoni grown under different nitrogen (N) rates. A pot trial in open air conditions was set up in 2012 with the aim to evaluate the effect of four N rates on the biometric and productive characteristics, steviol glycoside (SG) content as well as on leaf gas exchanges, chlorophyll fluorescence, photosynthetic pigments, Rubisco activity and N use efficiency. N deficiency caused a decrease in leaf N content, chlorophylls and photosynthetic CO2 assimilation, resulting in a lower dry matter accumulation as well as in reduced SG production. The application of 150 kg N ha − 1 seems to be the most effective treatment to improve rebaudioside A (Reb A) content, Reb A/stevioside ratio, photosynthetic CO2 assimilation, stomatal conductance, N use efficiency, ribulose-1, 5-bis-phosphate carboxylase/oxygenase (Rubisco) and PSII efficiency. The results demonstrate that by using an appropriate N rate it is possible to modulate the SG biosynthesis, with a significant increase in the Reb A content and in the ratio between Reb A and stevioside. This finding is of great relevance in order to obtain a raw material designed to meet consumer needs and bio-industry requirements for high-quality, Reb A content, and safe and environmentally friendly products.